Consequences of Riding Takeover Waves: Australian Evidence - Duong, Lien; Izan, H. (Wiley-Blackwell Publishing Asia, 2012)
This paper uses Australian data to analyze takeover bid premiums and long-term abnormal returns for mergers that occur during wave and non-wave periods. Findings reveal that bid premiums are slightly lower in wave periods, and bidding firms earn normal post-takeover returns (relative to a portfolio of firms matched on size and survival) if their bids were made in non-wave periods. However, bidders who announced their takeover bids during wave periods exhibit significant underperformance. For mergers that took place within waves, there is no difference in bid premiums nor is there a difference in the long-run returns of bidders involved during the first half and second half of the waves. We find that none of prominent theories of merger waves (managerial, misvaluation, and neoclassical) can fully account for Australian takeover waves and their effects. Instead, our results suggest that Banal-Estanol et al.'s screening theory of merger activity, by combining the misvaluation and neoclassical theories, may provide a better explanation.